2019
DOI: 10.1108/ijhma-07-2019-0077
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the effects of price fairness and Islamic altruism with the TPB model

Abstract: Purpose The purpose of this study is to examine the impacts of price fairness and Islamic altruism on the Islamic mortgage adoption along with theory of planned behaviour’s (TPB’s) constructs (i.e. attitude, subjective norm and perceived behavioural control). Attitude is also analysed as a mediator in this study. Design/methodology/approach Using TPB as a baseline theory, this study analyses the Islamic mortgage adoption involving a total of 281 Muslim consumers in Malaysia using partial least squares. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 39 publications
4
27
0
1
Order By: Relevance
“…Logically, the stronger the subjective norms are, the higher the probability of intention to perform a particular behaviour. Additionally, other studies have confirmed and emphasized that peer groups, family and friends play a necessary role in selecting and promoting Islamic banking and finance (Erol and El-Bdour, 1989;Hamid and Masood, 2011;Sayuti and Amin, 2019;Metawa and Almossawi, 1998).…”
Section: Subjective Normmentioning
confidence: 93%
See 2 more Smart Citations
“…Logically, the stronger the subjective norms are, the higher the probability of intention to perform a particular behaviour. Additionally, other studies have confirmed and emphasized that peer groups, family and friends play a necessary role in selecting and promoting Islamic banking and finance (Erol and El-Bdour, 1989;Hamid and Masood, 2011;Sayuti and Amin, 2019;Metawa and Almossawi, 1998).…”
Section: Subjective Normmentioning
confidence: 93%
“…This coincided with the obligation to pay zakah, being one of the five pillars of Islam (Huda et al, 2012). PBC has also been found to be significantly related to consumer acceptance for Islamic banking and finance products (Amin, 2013;Amin et al, 2014a, 2014c, Sayuti and Amin, 2019. In another study of Muslim consumers' decision to patronize halal store, the results revealed that PBC depends on past experience and also upon things that facilitate their action (Mohd Suki et al, 2014).…”
Section: Perceive Behavioural Controlmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, note that the role of the religious satisfaction variable serves as a source of mediator and not of moderator in the preferences of the clients for financing. Some researchers even conclude that between the justice perception and preferring such financing methods, the religious satisfaction factor plays a role of absolute regulation (Al-Omar & Abdel-Haq, 1996;Wajdi Dusuki, 2008;Amin, 2019;Sayuti & Amin, 2019). However, of the other factors tested, it is also concluded that the financial fairness and welfare factors have no significant impact upon the preferences for the interestfree housing financing.…”
Section: The Theory Of Fair Consumer Behaviormentioning
confidence: 99%
“…Much research was performed for insights into the factors that should be prioritised by financial institutions for marketing strategies, customer behaviours and bank attributes (reputation, products, services and pricing). Regardless, systematic empirical works on the subject area for a comprehensive depiction of current literature remained lacking (Sayuti et al , 2020; Razak et al , 2020; Sayuti and Amin, 2019; Yi and Zhongkai, 2018; Zabri and Mohammed, 2018; Amin and Hamid, 2018; Amin et al , 2017; Amin, 2017b; Ibrahim et al , 2017; Amin et al , 2016; Basri et al , 2016; Amin et al , 2014a; Amin et al , 2013; Alam et al , 2012; Taib et al , 2008; Mohamed Imtiyaz et al , 2017). Despite the availability of various literature review methodologies, the systematic literature review (SLR) outweighs typical literature counterparts that are rife with various issues involving reviewer and selection bias and broad selection (Robinson and Lowe, 2015).…”
Section: Introductionmentioning
confidence: 99%